1991
DOI: 10.1159/000129139
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cationic Elastase in Porcine Experimental Pancreatitis

Abstract: A radioimmunoassay for porcine, cationic, pancreatic elastase (irPE) is described. Normal porcine serum contains only small amounts of irPE (<3 µg/l). IrPE in serum and peritoneal exudate from 6 pigs with experimental pancreatitis was found mainly in a molecular form corresponding to free pro-enzyme. The presence of α1-, α2-macroglobulin-bound elastase-like enzymatic activity in the peritoneal exudates from pigs with pancreatitis, however, indicates that the proteinase is to some extent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This usually results in a dose-response curve that is nonparallel to the standard curve, which these authors also re ported [21]. The low recovery of active tissue kallikrein when added to plasma and perito neal fluid in this study, and previously also reported in the rat and human [22,23], indi cates that such complex formation takes place, even though it has been reported that porcine tissue kallikrein does not bind to alpha-macroglobulins [24], However, the larg er recovery of active tissue kallikrein from normal peritoneal fluid compared with plas ma supports the theory of alpha-macroglobulin complexes masking the immunoreactivity, as the level of alpha-macroglobulins in normal porcine peritoneal fluid is only about 10% of that in plasma [11,13]. Furthermore the a Fig.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This usually results in a dose-response curve that is nonparallel to the standard curve, which these authors also re ported [21]. The low recovery of active tissue kallikrein when added to plasma and perito neal fluid in this study, and previously also reported in the rat and human [22,23], indi cates that such complex formation takes place, even though it has been reported that porcine tissue kallikrein does not bind to alpha-macroglobulins [24], However, the larg er recovery of active tissue kallikrein from normal peritoneal fluid compared with plas ma supports the theory of alpha-macroglobulin complexes masking the immunoreactivity, as the level of alpha-macroglobulins in normal porcine peritoneal fluid is only about 10% of that in plasma [11,13]. Furthermore the a Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Another possible explana tion for the low recovery is the loss of immunoreactivity of the active tissue kallikrein due to enzymatic proteolysis of the kallikrein mol ecule by enzymes present in plasma [26,27], Bile-induced, experimental pancreatitis is thought to resemble bilestone-associated pan creatitis in man, although some authors con- sider that the model has some shortcomings [28]. Our experimental models are well-stan dardized models [12] and have been used by us in several earlier studies [11,13]. The addi tion of trypsin to the injected bile results in a more severe pancreatitis and enhanced mor tality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation